Language acculturation and identity construction: A narrative inquiry of Filipino teachers in Indonesia - Molina, Merry Luz; Tambunan, Anna Riana Suryanti; Ariatna (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
While language, identity, and acculturation have been widely examined, limited research has explored how Filipino migrant teachers in Southeast Asia, particularly in Medan, Indonesia, construct their identities through everyday language experiences. This study investigates how Filipino migrant teachers negotiate identity through language acculturation. Grounded in Identity Theory and informed by perspectives on language identity and acculturation, the study employed a qualitative Narrative Inquiry design involving five Filipino migrant teachers. Data were collected through narrative interviews and photovoice, then analyzed using thematic analysis. The findings reveal that identity is dynamic and continuously reshaped through language acculturation. Initially, participants experienced diminished confidence due to limited proficiency in Bahasa Indonesia, affecting their professional self-perception. As they gradually acquired and used the language in daily interactions, they regained confidence and reconstructed their identities. Ultimately, language functioned as a bridge that fostered belonging while integrating their Filipino identity with their lived experiences in Indonesia.